Breast cancer mortality trend in Portugal (1955-2002). - Bastos, Joana (2007)
In the last decade there were significant changes in breast cancer mortality that is declining since the 90 s in several countries. The aim of this study was to quantify the variation of the female breast cancer mortality rates, in Portugal and in different regions of the country, considering the changes in the trends.Breast cancer mortality rates and the number of deaths were obtained from the World Health Organization, for the years from 1955 to 2002, and the number of deaths and population in each region were obtained from the publication Risco de Morrer em Portugal. Age-standardized rates were computed by the direct method, using the European standard population. Joinpoint regression analyses were performed to identify the years in which changes in trends have occurred, and to estimate the annual percent changes in each period, for the age groups 35-74, 35-44, 45-54, 55-64 and 65-74 years. The annual variation was computed for each Portuguese region from 1990 to 2002.Breast cancer mortality rates increased 1.55%/year (95% Confidence Interval (CI): 1.43 to 1.68) between 1955 and 1992 and changed -2.02%/year (95%CI: -2.81 to -1.31) from 1992 to 2002 in women aged 35 to 74 years. No significant differences were observed in the joinpoints or the estimated annual percent changes across age strata. At a regional level, the mortality trends between 1990 and 2002 were inversely associated with the rates at the beginning of this period (r= -0.74, p